Kirigami‐Inspired 3D Organic Light‐Emitting Diode (OLED) Lighting Concepts. Issue 7 (12th June 2018) - Kim, Taehwan; Price, Jared S.; Grede, Alex; Lee, Sora; Choi, Gihoon; Guan, Weihua; Jackson, Thomas N.; Giebink, Noel C.
Abstract: As the technical performance and reliability of white organic light‐emitting diodes (OLEDs) begin to mature, broader adoption in the lighting market will increasingly rely on exploiting the unique aesthetic opportunities that OLEDs afford. Here, kirigami‐based concepts that enable ultraflexible thin film OLEDs to be cut, folded, and "popped up" into a variety of 3D shapes ranging from globes to candle flame mimics are used. It is demonstrated that large area (>15 cm 2 ) OLEDs fabricated and encapsulated on sub‐50 µm thick polyimide films can be cut and folded into 3D with negligible impact on their efficiency and electrical characteristics. These results point to an alternate paradigm for OLED lighting that moves beyond traditional 2D panels toward 3D designs that deliver unique and creative new opportunities for lighting. Abstract : Flexible 3D organic light‐emitting diode (OLED) lighting concepts are demonstrated using a kirigami‐based approach to cut, fold, and "pop up" traditional planar OLEDs into a variety of intricate shapes ranging from globes to candle flame mimics.